Dual biologic therapy for the treatment of rheumatic diseases and asthma: a case series. Issue 1 (3rd February 2023) - Malik, Mariam; Jones, Bryony; Williams, Emma; Kurukulaaratchy, Ramesh; Holroyd, Chris; Mason, Alice
Abstract: Objective: Combination biological therapies are being considered increasingly for patients with multiple co-morbidities requiring biologics. There are limited data available on this approach, and concerns remain about the possible risk of adverse events, particularly infection. Methods: We present three patients on dual biologics for rheumatic disease and asthma. The biologic combinations used were etanercept and mepolizumab, infliximab and omalizumab, and etanercept and omalizumab. The time on combination biologic therapies ranged from 24 to 36 months. Patients were monitored for any serious adverse events. Results: All three patients were able to tolerate combined biologic therapies, with no serious adverse events. All three patients gained improvement in their rheumatic and asthma disease control, with reduction in disease activity scores and reduction in steroid usage. Conclusion: The decision to start dual biologic therapy should be considered carefully, on a case-by-case basis. The number of patients who are on combination biological therapy is small, and data are sparse. Real-world data are needed to examine the long-term benefits and risks of different forms of combination biologic therapies. Lay Summary: What does this mean for patients? Biological therapies are specific therapies that target particular parts of the immune system. These medications are used in the treatment of autoimmune conditions, such as rheumatoid arthritis (RA). In RA, they work by stopping particular chemicals in the blood from activating the immune system to attack joints. They are very effective medications to treat inflammatory autoimmune conditions. In some cases, they can be associated with side effects, particularly increased risk of infections. We have written a case series about three people who have inflammatory autoimmune conditions and are receiving two biologics to treat these. All three people have inflammatory arthritis and asthma and are receiving two different biological therapies. They have been receiving these for a period ranging from 24 to 36 months. All three people have been able to tolerate combined biologic therapies, with no serious adverse events thus far. They have gained improvement in their arthritis and asthma control, with reduction in disease activity and the use of steroids. Although the number of people receiving more than one biological treatment is small, this study suggests that dual therapy could be used in certain situations. The decision to start dual biologic therapy should be considered carefully, on a case-by-case basis, by the specialists.